Perancangan Aplikasi Pembelajaran “Fruvenimal” Berbasis HTML5 - Teddy Satria; Adian Fatchur Rochim; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2015)
Golden Age is the time when a child's brain's ability to absorb information is very high. All information supplied will influence the child in later. Technology gives an effect on the progress of children. Computer technology can be a fun learning media and interseted for kid. Therefore, Fruvenimal application is developed as a learning media for introducing fruits, vegetables, and animals from the name, shape, sound, and vitamin via multimedia applications. Fruvenimal application is built using Construct 2. Multimedia aplication development used Multimedia Development Life Cycle (MDLC) which consists of six stages: concept, design, collection of material, manufacture, testing, and distribution /evaluation. For application testing method using the black box Test. Results from this study in the form of a multimedia application named Fruvenimal that can run on HTML5 browser. The application can be a learning media to introduce of fruits, vegetables, and animals for people, especially aged <8 so that kid from an early age is able to recognize the diversity of fruits, vegetables, and animals on earth.